2011
DOI: 10.3233/jad-2011-110140
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Glutathione Peroxidase and Inhibition of p53-Related Apoptosis by Apomorphine

Abstract: Apomorphine hydrochloride (APO) is known to be a dopamine receptor agonist, and has recently been found to be a novel drug for Alzheimer's disease (AD). We found that APO treatment ameliorated oxidative stress in an AD mouse model and specifically attenuated the hydrogen peroxide-induced p53-related apoptosis in the SH-SY5Y neuroblastoma cell line. To further understand the mechanism behind this action, we investigated the actions of APO on intracellular redox systems, such as the glutathione cycle and catalas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…This suggests that the addition of APO to MPP + -treated SH-SY5Y cells could reduce ROS levels. It was reported that APO treatment increases GPx (glutathione peroxidase), which can detoxify ROS such as H 2 O 2 (Ma et al 2011). This indicates that the induction of HIF1A might be more difficult in MPP +treated SH-SY5Y cells with APO rather than SH-SY5Y cells treated with MPP + alone.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the addition of APO to MPP + -treated SH-SY5Y cells could reduce ROS levels. It was reported that APO treatment increases GPx (glutathione peroxidase), which can detoxify ROS such as H 2 O 2 (Ma et al 2011). This indicates that the induction of HIF1A might be more difficult in MPP +treated SH-SY5Y cells with APO rather than SH-SY5Y cells treated with MPP + alone.…”
Section: Discussionmentioning
confidence: 99%
“…They involve trophic factor induction (BDNF Guo et al, 2002;FGF-2 Li et al, 2006;GDNF Ohta et al, 2000, Guo et al, 2002NGF Ohta et al, 2000), radical scavenging (Ubeda et al, 1993;Hara et al, 2006), metal scavenging (Ubeda et al, 1993;Youdim et al, 1999), oxidant and antioxidant activity (Ubeda et al 1993;Gassen et al 1996Gassen et al , 1998Grünblatt et al, 1999aGrünblatt et al, , 1999bGrünblatt et al, , 2001dos Santos El Bacha et al 2001;Battaglia et al, 2002;Kyriasis, 2003;Pardini et al 2003 ;Mandel et al, 2004;;Picada et al, 2005 ;Castri et al, 2006;Hara et al, 2006;Himeno et al, 2011;Ma et al, 2011), activation of anti-inflammatory pathways (Hara et al, 2006) and apoptosis modulation (Gassen et al, 1996;Pardini et al 2003. Depending on the dose, duration and cell types, apomorphine can therefore be cytoprotective, cytostatic or even cytotoxic.…”
Section: Pharmacological Targets Of Apomorphinementioning
confidence: 99%
“…Apomorphine was also shown to reduce oxidative stress in 3xTg-AD mice, as well as in a human neuroblastoma cell line (SH-SY5Y), by targeting p53-related apoptosis and enhancing glutathione peroxidase (GPx) activity, among other possible mechanisms (Himeno et al, 2011;Ma et al, 2011). These effects were not limited to intracellular changes: when administered subcutaneously to 3xTg-AD mice once a week for one month (5-20 mg/kg), apomorphine even improved short-term memory function, the best results being obtained with a dose of 5mg/kg (Himeno et al, 2011).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…These findings also suggest that the neuroprotective action may involve other pathways rather than activation of DA receptors. Among the proposed mechanisms of action are its radical scavenging activity [13,15,18,19] and iron chelating properties [20], inhibi-Involvement of CRH Receptors in the Neuroprotective Action of R-Apomorphine in the Striatal 6-OHDA Rat Model tion of mitochondrial iron-induced lipid peroxidation and protein oxidation [13,18,19], activation of nuclear transcription factor NF-E2-related factor 2 (Nrf2) [21], inhibition of monoamine oxidase (MAO)-A and MAO-B [22], its enhancement of glutathione peroxidase activity [23], anti-apoptotic [7,24], anti-inflammatory [9], mitogenic [25] and trophic effects [26][27][28][29]. We previously showed that a short-term treatment with R-apomorphine (10 mg/kg/day, s.c., during 11 days), started before or 24 hours after lesions, has neuroprotective actions in the striatal 6-OHDA rat model, as demonstrated by an improved motor behavior and a significant protection (20% -35%) of the integrity of the nigrostriatal dopaminergic system at the level of the substantia nigra pars compacta and striatum [14].…”
Section: Introductionmentioning
confidence: 99%